Comparative effects of open-skill and closed-skill sports on executive function in university students: a 16-week quasi-experimental study - Li, Yu-fan; Gao, Tianyu; Luo, Li-peng; He, Shan (Frontiers in Psychology, 2024)
Introduction Previous reviews have often concluded that open-skill sports are more effective at enhancing executive function (EF) than closed-skill sports. However, this conclusion may not hold for closed-skill sports with high cognitive demands, such as golf. This study aimed to compare the effects of football (open-skill) and golf (closed-skill) training on enhancing EF in university students. Method Using a quasi-experimental, pre-post test design, 63 male participants were assigned to three groups: football (n = 21), golf (n = 21), and a sedentary control group (n = 21). Over 16 weeks of training, the intervention groups engaged in four 90-min training sessions per week, while the control group attended one 80-min physical education class per week. Assessments were conducted before and after the intervention. EFs, including inhibition control and working memory, were assessed using the Flanker task and Corsi-block tapping task, respectively. Cardiovascular fitness (CRF) was measured by the multi-stage fitness test. Results The golf group showed significant improvements in inhibition control from pre- to post-intervention (p = 0.02, d = 0.26), while the football and control groups did not exhibit significant changes. Post-intervention comparisons indicated no significant differences in EF performance between the golf and football groups; however, both outperformed the control group (golf, p = 0.002, d = 0.99; football, p = 0.01, d = 0.67). No significant improvement was observed in working memory for any group. Additionally, changes in CRF were not significantly correlated with EF performance. Conclusion This study provides preliminary evidence that golf, a closed-skill sport with high cognitive demands, can effectively improve inhibitory control after 16 weeks of training. This improvement is comparable to that observed in football, an open-skill sport. The findings also suggest that the cognitive demands of the sports, rather than improvements in physical fitness, may be primarily responsible for the enhancements in EF.